Comparative Genre Analysis of Lyrical Novels: Christian and Kid and To the Lighthouse - Parnian Zarepoor; Najmeh Dorri; Gholamhosein Gholamhoseinzade (مطالعات زبانی و بلاغی)
This research aims at identifying the criteria of genre analysis in lyrical novels, specifically a comparative study of Christian and Kid by Houshang Golshiri and To the Lighthouse by Virginia Woolf. This is a descriptive-analytical research based on library resources. In this process, the main features of lyrical poetry, as the origin of the lyrical genre, have been compared based on theories proposed by Ralph Freedman, who initiated the discussion on lyrical novel in world literature. In this regard, five intratextual and extratextual genre analysis factors of the novel have been considered: formal and content-related factors (content, color and plot, narrator and point of view, character and characterization, language and tone, and scene), the relationship of the work with discourses, external function of the work, and audience. The results of examining genre analysis factors have been measured with the components of the lyrical genre. According to the research findings, the aforementioned novels belong to the lyrical genre. The genre analysis of these novels reveals the following: formal and content-related features serve the lyrical components (introspection and highlighting); they correspond with psychological novels and the stream of consciousness; modernist discourse predominantly prevails in them. During periods of sociopolitical turmoil or time of stability and overcoming basic life needs, the works whose authors tend to introspect, are more prevalent. They have individual and artistic external functions; their readers are active and engaged in internal identification with the character. Accordingly, the position of genre analysis of the two Persian and English lyrical novels becomes clear.